Rutin as promising drug for the treatment of Parkinson's disease: an assessment of MAO-B inhibitory potential by docking, molecular dynamics and DFT studies. Issue 18 (12th December 2019) - Azam, Faizul; Abodabos, Honiwa Suliman; Taban, Ismail M.; Rfieda, Abdalla R.; Mahmood, Danish; Anwar, Md Jamir; Khan, Shamshir; Sizochenko, Natalia; Poli, Giulio; Tuccinardi, Tiziano; Ali, Hamed I.
ABSTRACT: Inhibitors of monoamine oxidase (MAO)-B have been used for many years in the therapy of Parkinson's disease (PD). Owing to the safety concerns of the currently used agents, the discovery of novel scaffolds is of considerable interest. MAO-B inhibitory potential of rutin, a flavonoid derived from natural sources, has been established in experimental findings. Hence, the current study seeks to examine the interactions between rutin and crystal structure of human MAO-B enzyme. Molecular docking calculations, as well as molecular dynamics simulations, were employed to investigate the binding mode and the stability of the rutin/MAO-B complex. Energies of highest occupied/lowest unoccupied molecular orbitals were computed through DFT studies and used to calculate electron affinity, hardness, chemical potential, electronegativity, and electrophilicity index in order to investigate the capability of these parameters to influence the ligand–receptor interactions. It was found that rutin traverses both the entrance cavity and the substrate cavity, forcing the Ile-199 'gate' to rotate into its open conformation. It results in the fusion of the two cavities of the MAO-B binding site and directly leads to better binding interactions. Results of the current study can be used for lead modification and development of novel drugs for the treatment of PD.